How Protein Depletion Balances Thrombosis and Bleeding Risk in the Context of Platelet's Activatory and Negative Signaling - Montecino-Garrido, Hector; Trostchansky, Andres; Espinosa Parrilla, Maria Yolanda; Palomo, Ivan; Fuentes, Eduardo (My University, 2024)
Platelets are small cell fragments that play a crucial role in hemostasis, requiring fast response times and fine signaling pathway regulation. For this regulation, platelets require a balance between two pathway types: the activatory and negative signaling pathways. Activatory signaling mediators are positive responses that enhance stimuli initiated by a receptor in the platelet membrane. Negative signaling regulates and controls the responses downstream of the same receptors to roll back or even avoid spontaneous thrombotic events. Several blood-related pathologies can be observed when these processes are unregulated, such as massive bleeding in activatory signaling inhibition or thrombotic events for negative signaling inhibition. The study of each protein and metabolite in isolation does not help to understand the role of the protein or how it can be contrasted; however, understanding the balance between active and negative signaling could help develop effective therapies to prevent thrombotic events and bleeding disorders.
Keywords: platelets; signaling; inhibitory; activatory; bleeding